PEMBERDAYAAN WANITA: PELATIHAN DAN MANAJEMEN LAKTASI PADA IBU BEKERJA DI INSTITUSI PENDIDIKAN DI MEDAN - Imelda, Fatwa; Darti, Nur Afi (Jurnal Riset Hesti Medan, 2019)
Breast Milk  is one of the world health organization programs. The profile of Indonesia's health data for 2015 shows the scope of administration. Exclusive breastfeeding in Indonesia is still low, the percentage of infants breastfeeding exclusively 0 to 6 months is 55.7% lower than in 2011, which was 61.5%. Some of the problems related to achieving exclusive breastfeeding in North Sumatra Province are that there are still many institutions that employ women not giving an opportunity for mothers who have babies 0-6 months to carry out exclusive breastfeeding as evidenced by the unavailability of lactation rooms and supporting devices; and there are still many health workers at the service level who have not cared for or have not side with the fulfillment of the baby's right to get exclusive breastfeeding. For this reason, the team from the Universitas Sumatera Utara, Faculty of Nursing sought to increase the coverage of exclusive breastfeeding specifically by making facilities for breastfeeding mothers and increasing breastfeeding knowledge and skills through community service about Lactation Management. All mothers have the knowledge and ability to carry out lactation management. It is expected by these two educational institutions, so that the team can continue to carry out community service in these two places.Keywords: women's empowerment, lactation management